2018
DOI: 10.18203/2320-6012.ijrms20180278
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific serum prostate-specific antigen references range among healthy men in Port Harcourt, Nigeria: a retrospective hospital-based study

Abstract: Background: Total prostate-specific antigen (PSA) levels increase with advancing age. Its age-specific ranges are being advocated to increase its sensitivity and specificity. This study was aimed to examine the relationship between total PSA levels and age, and to determine the age-specific ranges among healthy men without prostatic diseases in our environment.Methods: In this retrospective hospital-based study, records of men without prostatic diseases who had visited University of Port Harcourt Teaching Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
(35 reference statements)
1
9
1
Order By: Relevance
“…In this study, the 95 th percentile cuff-off serum PSA value increased steadily from 2.89 ng/ml in the <40 years category to7.0 ng/ml in the ≥70years category (see Figure 2). This trend was also replicated in other Nigerian studies (Amadi and Odum, 2018;Al-Abdin andAl-Beeshi, 2018). However, the mean PSA values obtained in this study were about two to two and half times higher than values reported by some researchers in the western world (Luboldt et al, 2007;Heidegger et al, 2015) .…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In this study, the 95 th percentile cuff-off serum PSA value increased steadily from 2.89 ng/ml in the <40 years category to7.0 ng/ml in the ≥70years category (see Figure 2). This trend was also replicated in other Nigerian studies (Amadi and Odum, 2018;Al-Abdin andAl-Beeshi, 2018). However, the mean PSA values obtained in this study were about two to two and half times higher than values reported by some researchers in the western world (Luboldt et al, 2007;Heidegger et al, 2015) .…”
Section: Resultssupporting
confidence: 81%
“…Al-Abdin and Al-Beeshi (2018) claimed that in blacks the prostate volume is larger than in Caucasians age for age. In the current study, the mean serum PSA values in the 40-49 years (2.09ng/ml) and 60-69years (2.63ng/ml) age categories were higher than that of the 50-60 years (1.99ng/ml) and ≥70years (2.59ng/ml) categories respectively against expectations based on the findings of similar studies (Ganpule and Dessai, 2007;Ikuerowo et al, 2016;Amadi and Odum, 2018;Al-Abdin andAl-Beeshi, 2018) .…”
Section: Eboreime Oo; Atoe Kcontrasting
confidence: 63%
See 2 more Smart Citations
“… 5 - 7 In Nigeria, the currently and widely accepted PSA reference interval is 0–4 ng/ml. 8 This reference interval value was informed by reference intervals derived from studies amongst Caucasians and other racial groups, 9 considering that there is scanty data on the subject from our local population 8 , 10 , 11 and notwithstanding the well-documented evidence of the influence of race and ethnicity on PSA levels. 12 - 14 …”
Section: Introductionmentioning
confidence: 99%